Is a multi-country genetic evaluation for Africa feasible? - Rege, J.E.O.; Westhuizen, J. van der (1998)
The need for, potential benefits of, and possible problems with the establishment of a multi-country genetic evaluation scheme for Africa are discussed. The most compelling argument for such a scheme is the opportunity it may provide for the genetic improvement of indigenous livestock populations and the possibility to open up new markets for African germplasm as well as inter-country germplasm trade within the continent. Other advantages may include the evaluation of imported, non-indigenous germplasm in the African environment and production systems, expansion of testing capacity by pooling resources, and possibility to account for genotype x environment interactions in genetic evaluations.